The Importance of Brand Awareness and Brand Loyalty in assessing Purchase Intentions of Consumer : A lesson from Xiaomi Phone Consumer - Rio Adi Surya (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aims to analize the effect of Brand Awareness and Brand Loyalty in assessing Purchase Intentions on Consumer  of Xiaomi phone. The research is explanatory research which explains the causal relation between the variables through hypothesis testing. The data collection technique used questionnaires and literature research. This research used 105 samples of Xiaomi phone consumers in Malang. Those samples were taken using a purposive sampling technique. Test instrument that was used for testing the research instrument are validity test and reliability test. The analytical methods that were used are path model analysis using SPSS 21. The result shows that Brand Awareness has significant and direct effect toward Brand Loyalty. Brand Awareness  also has significant and direct effect toward Purchase Intention. But, Brand Loyalty has no significant and direct effect toward Purchase Intention. Moreover, Brand Awareness undirectly affect to Purchase Intention through Brand Loyalty as mediatorKey Words: Brand, Brand Awareness, Brand Loyalty, Purchase Intention